Portable and simple electroanalytical procedure for simultaneous detection of dipyrone and norfloxacin with disposable commercial electrodes in water and organic fertilizers - Silva, Luiz R. G.; Rodrigues, José G. A. [UNESP]; Vasconcellos, Maria de L. S.; Ribeiro, Emerson S. [UNESP]; D’Elia, Eliane [UNESP]; Ferreira, Rafael de Q. (Springer Nature, 2022)
The increasing presence of drugs in the environment has caused great concern in recent years due to their adverse side effects, whether related to animals or humans. In this aspect, the search for methods capable of controlling and monitoring these emerging contaminants in a simple, fast, low-cost, and environmentally friendly way becomes a very important research area that can assist in the preservation of the environment and human health. Therefore, the present work aims to propose for the first time the simultaneous electroanalytical quantification of two drugs, extremely consumed worldwide (dipyrone and norfloxacin) of different classes (analgesic and antibiotic), in environmental and biological samples (organic fertilizer, water, and urine). For this, a commercial disposable boron-doped diamond electrochemical sensor (screen-printed electrodes) was used, in conjunction with portable equipment. A simple procedure was fully optimized for the determination of these two analytes by square wave voltammetry (SWV), including the choice of the best working pH and operational parameters of the technique. The SWV operational parameters were optimized using unified multivariate optimization for the best analysis condition for both drugs. The proposed method presents limit of detection of 0.30 and 0.40 µmol L−1 for dipyrone and norfloxacin, respectively. The analysis of the samples showed a recovery ranging from 94.0 to 105.0%, demonstrating that the method is suitable for performing the simultaneous determination in a few seconds, with no need for sample pre-treatment steps, and in a sustainable way.
Keywords: Drugs; Electrochemistry; Emerging contaminants; Organic fertilizer; Screen-printed electrode